TINJAUAN KESEGARAN JASMANI TERHADAP SISWA EKSTRAKURIKULER BOLAVOLI SMK NEGERI 1 SUNGAI LILIN - Sugar Wanto (STKIP ROKANIA, 2017)
This study aims to find information about the physical fitness level of students ekstrskurikuler volleyball SMK N 1 river wax. By measuring the level of physical fitness using Physical Freshness Test Indonesia (TKJI) for children aged 16 years, were carried out during the first day. Samples are 25 people with the sampling technique used purposive sampling. The method used in this research is descriptive with test and measurement techniques. Based on the results of the study 25 students extracurricular SMK N 1 river candle unknown male student with the lowest score 17, highest score 20, the average value of the standard deviation of 18.87 and 1:02. While female student with the lowest score 14, highest score 16, the average value of 15.09 and a standard deviation of 0.54. Image data sets in generalphysical fitness level of 25 students in extracurricular volleyball SMK 1 river candle physical fitness level data 14 male students comprised 13 people categorized as good and 1 category were, for the physical fitness level of 11 students comprised 11 people categorized daughter was